Xanthomonas effector XopR hijacks host actin cytoskeleton via complex coacervation - He Sun (Nature Portfolio, 2021)
Bacterial pathogens can subvert host cell processes through secreted proteins but the precise mechanisms and repertoire of proteins remains unclear. Here the authors report that a bacterial effector protein of Xanthomonas campestris, XopR, undergoes liquid-liquid phase separation to hijack the host cell actin cytoskeleton.